Analiza slovenskih elektronskih kontinuiranih virov na spletu - Kodrič, Nataša (Knjižnica, 2005)
The present article is the result of a special study "gathering and archiving Slovenian internet resources" in the frames of the research program "Competency of Slovenia 2001-2006". The goal of the study was to find out the number of titles of electronic continuing resources existing only online in Slovenian ISSN database, to describe criteria for registration, to carry out an analysis of the publishers of these resources and to produce a bibliography of Slovenian electronic continuing resources from 1991 to 2003.
Keywords: kontinuirani viri; integrirni viri; serijske publikacije; založniki; bibliografije